Diagnostic utility of serological biomarkers in patients with Crohn's disease: A case–control study. Issue 32 (August 2018) - Yao, Fang; Fan, Yihong; Lv, Bin; Ji, Conghua; Xu, Li
Abstract : Abstract: The aim of this study was to examine the expression of serological markers in patients with inflammatory bowel disease in China, and determine the diagnostic utility of serological markers, individually and in combination, for the diagnosis and differential diagnosis of Crohn's disease (CD). Serum samples were obtained from 160 participants in Eastern China. Among the participants, 98 were diagnosed with CD, 33 had ulcerative colitis (UC), and 29 were healthy controls (HC). The serum samples were tested for the presence of antibodies against outer membrane porin C (anti-OmpC), Pseudomonas fluorescens bacterial sequence I2 (anti-I2 ), anti-laminarin (anti-L), anti-chitin (anti-C), anti-chitobioside carbohydrate antibody (ACCA), anti-laminaribioside carbohydrate antibody (ALCA), anti-mannobioside carbohydrate antibody (AMCA), and anti- Saccharomyces cerevisiae antibody (ASCA) by indirect enzyme-linked immunosorbent assay (ELISA). Individually, anti-C, anti-L, ASCA-IgG, and ALCA lacked diagnostic value in the differentiation of CD. ASCA-IgA remained the most accurate marker for the diagnosis of CD, with an area under the curve (AUC) of 0.77; however, its sensitivity and specificity were both lower than 75%. Among the combinations of the 5 markers with significant diagnosing ability for CD, combinations with any 2 of the 3 markers, ASCA IgA, AMCA, and ACCA positive, provided the best accuracy in the diagnosis and differential diagnosis of CD (sensitivity and specificity both above 75%) and had the highest Youden index. Serological antibodies, when considered in combination, have remarkable value in the diagnosis and differential diagnosis of CD. Especially, the combination of any 2 of the 3 markers, ASCA-IgA, AMCA, ACCA positive, appears to be optimal.